Feasibility of a new self‐expandable metallic stent for patients with malignant colorectal obstruction. Issue 2 (9th July 2012) - Yoshida, Shuntaro; Watabe, Hirotsugu; Isayama, Hiroyuki; Kogure, Hirofumi; Nakai, Yousuke; Yamamoto, Natsuyo; Sasaki, Takashi; Kawakubo, Kazumichi; Hamada, Tsuyoshi; Ito, Yukiko; Yashima, Yoko; Sasahira, Naoki; et al.
<x xml:space="preserve">Abstract</x> Aim Stent migration due to peristalsis of the colon is one of the unresolved complications of colonic self‐expandable metallic stent (SEMS) placement. Axial force (AF), a recovery force of the stent to a straight position after bending, has been considered a factor influencing the conformability of the digestive tract. An uncovered SEMS (Niti‐S Enteral Colonic Uncovered Stent, D‐type; Taewoong, Inc., Gimpo, South Korea) with improved conformability is considered to decrease migration. Methods Thirty three consecutive patients with symptomatic colorectal obstruction between March 2006 and December 2011 underwent endoscopic stent placement for palliation to estimate the efficacy and safety of Niti‐S stents prospectively in four tertiary referral centers. Results Technical and clinical success rates were 100% and 97%, respectively. Seventeen patients had the following complications: ingrowth (n = 6), overgrowth (n = 1), collapse of the SEMS (n = 1), stool impaction (n = 2), migration (n = 1), bleeding (n = 3), and tenesmus (n = 3). The patient with migration had no recurrent symptoms until death. Of these 17 patients, 10 required re‐interventions. Seven patients underwent an additional SEMS implantation. One patient underwent surgery for stoma creation. Two patients had stool impaction, and they underwent endoscopic cleaning. The median duration of patency was 347.0 ± 65.5 days. The mean survival time after stent insertion was 240.1 ± 39.9 days. Conclusion The new SEMS effectively relieves malignant colorectal obstruction. Good conformability, according to the very low AF, may contribute to the low incidence of migration.